The First Episode Rapid Early Intervention for Eating Disorders ‐ Upscaled study: Clinical outcomes. Issue 1 (29th March 2021) - Austin, Amelia; Flynn, Michaela; Shearer, James; Long, Mike; Allen, Karina; Mountford, Victoria A.; Glennon, Danielle; Grant, Nina; Brown, Amy; Franklin‐Smith, Mary; Schelhase, Monique; Jones, William Rhys; et al.
Abstract: Background: First Episode Rapid Early Intervention for Eating Disorders (FREED) is a service model and care pathway for emerging adults aged 16 to 25‐years with a recent onset eating disorder (ED) of <3 years. A previous single‐site study suggests that FREED significantly improves clinical outcomes compared to treatment‐as‐usual (TAU). The present study (FREED‐Up) assessed the scalability of FREED. A multi‐centre quasi‐experimental pre‐post design was used, comparing patient outcomes before and after implementation of FREED in participating services. Methods: FREED patients ( n = 278) were consecutive, prospectively ascertained referrals to four specialist ED services in England, assessed at four time points over 12 months on ED symptoms, mood, service utilization and cost. FREED patients were compared to a TAU cohort ( n = 224) of similar patients, identified retrospectively from electronic patient records in participating services. All were emerging adults aged 16–25 experiencing a first episode ED of <3 years duration. Results: Overall, FREED patients made significant and rapid clinical improvements over time. 53.2% of FREED patients with anorexia nervosa reached a healthy weight at the 12‐month timepoint, compared to only 17.9% of TAU patients ( X 2 [1, N = 107] = 10.46, p < .001). Significantly fewer FREED patients required intensive (i.e., in‐patient or day‐patient) treatment (6.6%) compared to TAU patients (12.4%) across the follow‐up period ( X 2 [1, N = 40] = 4.36, p = .037). This contributed to a trend in cost savings in FREED compared to TAU (−£4472, p = .06, CI −£9168, £233). Discussion: FREED is robust and scalable and is associated with substantial improvements in clinical outcomes, reduction in inpatient or day‐patient admissions, and cost‐savings.